2014
DOI: 10.1007/s40520-014-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability as a predictor of mortality and disability: cross-country differences in the survey of health, aging, and retirement in Europe (SHARE)

Abstract: Social vulnerability was a significant predictor of mortality and disability, though when controlling for frailty, this relationship varied by the social model of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 32 publications
4
81
0
13
Order By: Relevance
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies were considered of good quality, 42,47,53,57‐59,61,68,69,74,75,78,84,85,96,98,99 31 were fair quality, 15,37,38,40,41,44‐46,50,51,54,56,60,62‐67,72,76,77,79,81,83,86,88,91‐93,97 and 17 were poor quality 36,38,43,48,49,52,55,70,71,73,80,82,87,89,90,94,95 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, disability is a recognised mediator of frailty, with increased late‐life functional decline during Activities of Daily Living (ADL) 12 and Instrumental Activities of Daily Living (IADL) 13 . Growing evidence indicates that social vulnerability (SV) may work as an accelerating co‐factor on a frailty trajectory 14,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This informs theoretical knowledge of factors that have a positive influence on health and highlights new directions to improve outcomes for this vulnerable patient group. In the community setting, frail patients who have a high degree of social vulnerability are protected from mortality if they live in countries with social models that provide a high level of formalised support (Wallace, Theou, Pena, Rockwood, & Andrew, 2015), further demonstrating practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points out that the concept of socioeconomic status among the elderly is broad and includes other factors, such as occupation, income, wealth and place of residence (14) . A study carried out with elderly individuals to assess the relationship of frailty with income in Europe found that the elderly with higher income had lower prevalence of frailty (15) .…”
Section: Discussionmentioning
confidence: 99%